Se llega a la Educación Corporal haciéndose sensible a los signos del cuerpo (2011)
ABSTRACT: We have found ourselves with a problem from the beginning. To develop the issue does not depend on the ability to reveal what it is, but to insist on the ability to do something different with it. So, what can be the relationship of pedagogy as learning and genealogy as interpretation to get the empowerment –to exist, act, think, know–, about physical education in terms of becoming sensitive to body language? We consider and direct our look towards a covenant relationship of reciprocal complementarity, of mutual intensification. Here we will develop the implications of this question. Pedagogy as learning, involves the signs and the experience of transformation; and genealogy, leads to the question of the origin of values and the value of the origin that establishes a body, as opposed to absolute values. It is the search for sense according to the game of active and reactive forces that a body produces. Pedagogy with genealogy is fortified in a game of decoding and interpretation. It is a covenant relationship in which the growth of each rebounds, in constant evolution.